METHODS OF EFFECTIVE ORGANIZATION OF TEACHING OF MATHEMATICS BY USING THE PROBLEM-BASED TEACHING - Ilkhom Makhmudovich Zulfikharov; Ibaydullaev Tulanboy (International Journal of Innovative Technologies in Social Science, 2019)
In this article: strengthening the material-technical and informational base of higher education institutions, further improving the quality of teaching and learning processes in mathematics and independent learning by providing high- quality educational literature, modern teaching methods and educational technologies; the stages of changing of the student's perceptual activity related to solve problematic situations in the effective organization of math classes are analyzed.